KOMBINASI SUHU DAN WAKTU KEJUT PANAS TERHADAP KEBERHASILAN TRIPLOID IKAN SEURUKAN (Osteochilus sp.) - Akbar, Taufik; Ibrahim, Yusran; Saputra, Fazril; Khaidir, Khaidir (Universitas Teuku Umar, 2021)
The purpose of the research is to obtain the most desirable zygote age for the triploidization process using heat shock and to determine the growth performance of Seurukan fish breed as triploidized. The method used in this study is experimental method with a completely randomized design model, through 4 treatments, and 3 replications. P0: Normal spawning (control) P1: Temperature 42°C, zygote age 15 minutes old, temperature shock duration 2 minutes. P2: Temperature 42°C, zygote age 20 minutes old, temperature shock duration 2 minutes. P3: Temperature 42°C, zygote age 25 minutes old, temperature shock duration 2 minutes. The preferable hatching was found in P3 treatment with a zygote age of 25 minutes old and immersed duration for 2 minutes which was 91.27%. In addition, the highest survival rate was found in the control treatment which was 89.98% and the percentage of triploids successfulness was found in P2 with a zygote age of 20 minutes old and an immersed duration for 2 minutes which was 60%. The results present that the triploidization of Seurukan fish through a temperature shock of 42oC for 2 minutes at the zygote age of 20 minutes old after fertilization succeeded in inducing triploid fish. The optimum treatment that able to produce the highest triploid (60%) with a survival rate of 81.1% is a temperature shock of 42oC for 2 minutes at the zygote age of 20 minutes old after fertilization.